Understanding Programming Languages - Ben- Ari, M. (Jon Wiley and Sons, 2006)
The choice of a specific programming language is one of the most important factors that influence the ultimate adoption of a software system. This volume explains what languages are available, how language constructs are implemented, and the role of language in expressing abstractions.
Keywords: Programming Languages; Computer Programming; Programmiersprache -- Gesamtdarstellung